Peningkatan Kompetensi Mahasiswa Calon Guru Melalui Program Kampus Mengajar Angkatan ke-2 pada Tahun 2021 - Hikmawati Hikmawati; Gunawan Gunawan; Aminah Aminah; Lalu Budiman Arief Budiman (Universitas Hamzanwadi, 2021)
This study aims to improve the competence of prospective teacher students through the 2nd Batch Teaching Campus Program in 2021 at SMPN 19 Mataram. This activity was carried out at SMPN 19 Mataram with a total of 8 students from 5 study programs at FKIP University of Mataram. The activity was carried out for 5 months, with a total implementation time of 20 weeks starting from August to December 2021. This type of research is quantitative research. Data on improving the competence of prospective teacher students was obtained from a questionnaire with an assessment using a scale of 4. The number of questions in the questionnaire was 25. The competency criteria consisted of four categories, namely Very good (A), Good (B), Enough (C), and Poor (K). The increase in student competence from week 1 to week 20 is calculated using N-gain. The average value of student teacher competency is 83.7, which is in the Good (B) criteria. The N-gain value obtained is 70.7 which is in the high criteria. Thus, the competence of prospective teacher students will increase through the 2nd Batch Teaching Campus Program in 2021 at SMPN 19 Mataram.